Feeding Mexico: The Political Uses of Food since 1910 - Ochoa, Enrique C. (Rowman & Littlefield Publishers, 2001)
Winner of the 1998 Michael C. Meyer Manuscript Prize! Feeding Mexico: The Political Uses of Food since 1910 traces the Mexican government's intervention in the regulation, production, and distribution of food from the days of Cardenas to the recent privatization inspired by NAFTA. Professor Ochoa argues that the real goals of the government's food subsidies were political, driven by presidential desires to court urban labor. Many of the agencies and policies were hastily set in place in response to short-term political or economic crises. Since the goals were not to alleviate poverty, but to provide modest subsidies to urban consumers, the policies did not eliminate destitution or malnutrition in the country. Despite the minimal achievements of these interventionist policies, the State Food Agency provided a symbol of the state's concern for the workers. The elimination of the Agency in the 1990s prompted social protest and unrest. Feeding Mexico is the first study to examine the creation of networks to deliver food products, the relationship of these channels of distribution to the food crisis, and the role of the state in trying to ameliorate the problem. Based on exhaustive research of new archival material and richly documented with statistical tables, this book exposes the dynamics and outcome of social policy in twentieth-century Mexico.